Volume 1B: Combustion, Fuels and Emissions 2013
DOI: 10.1115/gt2013-95565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reduced Kinetics in Simulation of Gasified Biomass Gas Combustion

Abstract: It is essentially important to use appropriate chemical kinetic models in the simulation process of gas turbine combustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The combustion of such gas mixtures showed a reduction of NOx emissions during the combustion of CO and H 2 with air [30]. Furthermore, this gas mixture was recently investigated as an alternative fuel for reciprocating engines and gas turbines in the context of heat and/or electricity generation or co-generation processes [31,32]. The Computations Fluid Dynamics (CFD), which is low cost compared to experimental tests, has become a crucial tool for understanding the combustion process of the gas mixture and for controlling the emission levels.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion of such gas mixtures showed a reduction of NOx emissions during the combustion of CO and H 2 with air [30]. Furthermore, this gas mixture was recently investigated as an alternative fuel for reciprocating engines and gas turbines in the context of heat and/or electricity generation or co-generation processes [31,32]. The Computations Fluid Dynamics (CFD), which is low cost compared to experimental tests, has become a crucial tool for understanding the combustion process of the gas mixture and for controlling the emission levels.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the laminar flame speed (high-temperature chemistry) for the WD-2 is around 10% lower than that for the DRM-19 [115,122]. Since the flames are prone to showing more stabilities with a shorter ignition delay and a higher burning velocity, while the WD-2 (with a shorter ignition delay but also a lower flame speed) shows larger flame oscillations (shown in Figure 2.12 (b)), as compared to the DRM-19, therefore, it can be indicated that the flame speed is a primary factor in determining the above-discussed oscillating flame behaviours.…”
Section: Reaction Mechanismsmentioning
confidence: 86%